Business ethics - Lafazanidis, Iosif; Λαφαζανίδης, Ιωσήφ (2021)
This thesis is the result of a months-long research and understanding of the factors involved in ethical decision making process. It is not the first attempt -at least as this mentioned in literature- of model utilization of the likelihood of taking or not ethical decisions under certain factors applied as variables. The decision-making process, we could say that is a mixture of factors that contribute to the final result. It cannot be easily normalized, because each person is unique and makes decisions according to its own data, its own perceptions and taking into account many different factors that can either be similar from person to person or differ entirely. Moreover, the conditions under which a decision is taken, are separate and also differ from case to case. For example, the economic environment, as well as social perceptions, create a framework which is not in the same way understood by all people.